A study to correlate smear microscopy and rapid antigen detection techniques in the diagnosis of malaria - Khatija Shameem; Dr. T Jaya Chandra (Tropical Journal of Pathology and Microbiology, 2020)
Introduction: Malaria is an endemic, tropical protozoan infection caused different Plasmodium species. A study was conducted to find the correlation between the peripheral blood smear and antigen demonstration for the detection of malaria.Materials and Methods: Study was conducted in the Department of Microbiology, GSL Medical College for 6 months. Peripheral blood smear stained by Giemsa technique ad commercially available rapid antigen detection kits were used for the diagnosis of malaria. Smear preparation and staining were carried as per WHO guidelines and manufacturer guidelines were followed to perform the test.Results: Among 98 the clinically diagnosed malaria cases in this study, 69 (70.4%) cases were identified as malaria positive. Out of these, 68% (47) were positive by blood smear examination and 87% (60) were positive by kit method and in the positive cases 35 were male and 34 were female participants.Conclusion: Rapid diagnostic tests were more sensitive in the diagnosis of malaria. However, other confirmatory tests such as PCR should be considered because some clinically proved cases were missed.